Effect of hyperbaric oxygenation on the expression of glutathione peroxidase 4 and lactoperoxidase genes in the lung of isogenic mice after ischemia/reperfusion injury in the small bowel - Ikejiri,Adauto Tsutomu (2018)
Abstract Purpose: To evaluate the effect of hyperbaric oxygenation (HBO) on the expression of the genes antioxidant glutathione peroxidase 4 (Gpx4) and lactoperoxidase (Lpo) in the lung of mice subjected to intestinal ischemia and reperfusion (IIR). Methods: Control group (CG) in which were subjected to anesthesia, laparotomy and observation for 120 minutes; an ischemia and reperfusion group (IRG) subjected to anesthesia, laparotomy, small bowel ischemia for 60 minutes and reperfusion for 60 minutes; and three groups treated with HBO during ischemia (HBOG + I), during reperfusion (HBOG + R) and during ischemia and reperfusion (HBOG + IR). Studied 84 genes of oxidative stress by the method (RT-qPCR). Genes with expression levels three times below or above the threshold cycle were considered significantly hypoexpressed or hyperexpressed, respectively (Student’s t-test p<0.05). Results: Gpx4 and Lpo were hiperexpressed on IRG, showing a correlation with these genes with lung oxidative stress. Treated with HBO, there was a significant reduction on genic expression on HBOG+I. Conclusion: Hyperbaric oxygenation showed to be associated with decreased expression of these antioxidant genes, suggesting a beneficial effect on the mechanism of pulmonary oxidative stress whenever applied during the ischemia.